Sustainable development goals and corporate social responsibility - Shukurov Sherzod Kholmomin ogly (THE INNOVATION ECONOMY, 2026)
This article provides an in-depth analysis of the concept of social responsibility of international companies within the framework of Sustainable Development Goals. In the Global economy, sustainability principles are seen as a key factor in ensuring sustainable development in the economic, social and environmental sectors. In its activities, international companies are widely introducing the principles of ESG (Environmental, Social, Governance), not only improving financial performance, but also taking on social and environmental responsibility. As part of the study, the Sustainable Development Goals set by the United Nations were analyzed, as well as the experiences of leading international companies, reports from consulting companies such as Deloitte and McKinsey. And the decisions and decrees of the president of the Republic of Uzbekistan adopted in 2021 and 2022 serve as the legal basis for the adaptation of national business to international standards and the implementation of strategies aimed at Sustainable Development. The results of the study showed that companies that have actively introduced the concept of social responsibility are achieving long-term economic stability, while also playing a leading role in the protection of society and the environment. For national companies, mastering international experiences and practicing the principles of sustainable development are important in improving economic competitiveness and ensuring the socio-economic well-being of society.